TETRA Backhauling via Satellite: Improving Call Setup Times and Saving Bandwidth - Anton Donner; Jawad Ahmed Saleemi; Javier Mulero Chaves (Journal of Computer Networks and Communications)
In disaster management scenarios with seriously damaged, not existing, or saturated communication infrastructures satellite communications can be an ideal means to provide connectivity with unaffected remote terrestrial trunked radio (TETRA) core networks. However, the propagation delay imposed by the satellite link affects the signalling protocols. This paper discusses the suitability of using a satellite link for TETRA backhauling, introducing two different architectures. In order to cope with the signal delay of the satellite link, the paper proposes and analyzes a suitable solution based on the use of a performance enhancing proxy (PEP). Additionally, robust header compression (ROHC) is discussed as suitable technology to transmit TETRA voice via IP-based satellite networks.